Elevated mean platelet volume in oral lichen planus and increased blood urea nitrogen level in its red-form: an observational study - Hui Yao; Yiwen Deng; Guanhuan Du; Yufeng Wang; Guoyao Tang (BMC, 2021)
Abstract Background This retrospective observational study aims to assess platelet count, mean platelet volume (MPV), blood biochemical tests for liver and kidney function in Chinese oral lichen planus (OLP) patients. Methods Eighty pathologically confirmed OLP patients and 51 healthy controls were enrolled. Data on full blood count and biochemical tests were obtained from the electronic medical record system of the hospital. Results MPV was elevated in OLP patients compared to controls (10.68 ± 0.97 fL versus 10.33 ± 0.89 fL, P = 0.042) while platelet count showed no difference between them. Red-form OLP group had increased blood urea nitrogen (BUN, 5.24 ± 1.15 mmol/L versus 4.69 ± 0.98 mmol/L, P = 0.036) than white-form OLP group. By contrast, there were no differences between those two groups in the other variables including MPV, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and creatinine. In terms of C-reactive protein (CRP), 92.5% of the OLP patients had a value of less than 3.48 mg/L. Besides, 75% of the OLP patients were overweight with body mass index (BMI) more than 25 kg/m2. Conclusions These findings indicate MPV might play roles in inflammation in OLP. The red-form OLP might be associated with damage or reduction of kidney function.